OPTIMASI PROTEIN DAN TOTAL PADATAN TERLARUT DALAM EKSTRAK CACING TANAH (Lumbricus rubellus)[Optimization of Protein and Total Soluble Solids in Earthworm (Lumbricus rubellus) Extract] - Hidayat, Nur; Aminah, Siti; Rahmah, Nur Lailatul (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2018)
This study aimed to obtain N-Amino and Total Soluble Solids (TSS) in the extract earthworms. The material used is earthworm type Lumbricus rubellus with age about 40 days. The design used in this study was Response Surface Methods (RSM) with the Central Composite Design, consisting of two factors: the incubation time (2, 4, and 6 days) and the percentage of basic material (10, 15, and 20 %). This research was conducted by incubating earthworm juice with 4% NaCl solution in accordance with treatment of incubation time and percentage of basic material. The results showed that the optimal results obtained were soluble protein 7.51% and TPT 48.90% using 2 days incubation time and 15% earthworms.